Activated pyrolytic carbon black recovered and pre-purified from waste tyres and its use in production of composites for rubber industry, such as components of new tyres or new technical articles
The pyrolysis of carbon black by treating waste tires through heat treatment, acid purification and reactive gas activation, solves the problems of zinc, sulfur and silica contaminants, and achieves the effect of efficiently enhancing the rubber composite.
Patent Information
- Application Number
- CN202380088416.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-23
- Filing Date
- 2023-12-21
- Publication Date
- 2025-08-01
AI Technical Summary
The prior art is difficult to effectively remove pollutants such as zinc, sulfur and silica in the pyrolyzed carbon black in waste tires, resulting in environmental pollution risks and vulcanization kinetic interference when they are used as reinforcement materials in rubber composites, and the enhancement effect is poor.
The carbon black is pyrolyzed by heat treatment of waste tires in an inert atmosphere, followed by purification of zinc and sulfur with carboxylic acid or inorganic acid, and the silica is removed in combination with hydrofluoric acid, and the surface of the carbon black is activated using a reactive gas, and surface etching is performed to increase the surface area and active sites.
The enhanced performance of pyrolytic carbon black in waste tires is significantly improved, allowing it to exhibit similar or even better enhancement effects in rubber composites as traditional petroleum-based carbon black, while reducing the risk of environmental pollution.
Smart Images

Figure BDA0005461919610000021 
Figure BDA0005461919610000031 
Figure BDA0005461919610000081
Abstract
Description
[0001] The pyrolysis of waste tires produces carbon black, hereinafter also referred to as pyrolytic carbon black (hereinafter simply referred to as CBp in this specification). In particular, the CBp directly obtained by pyrolysis, called crude pyrolytic carbon black (hereinafter denoted by the abbreviation CBp-0 in this specification), is contaminated with pyrolytic rubber residues. These pyrolytic residues also contain a rich mixture of polycyclic aromatic hydrocarbons (PAHs), some of which are well-known carcinogens, and they are mixed in the asphalt-tar substances of the pyrolytic rubber residues [cf.: F. Cataldo, (2020). On the characterisation of carbon black from tire pyrolysis. Fullerenes, Nanotubes and Carbon Nanostructures, 28:368-376; F. Cataldo, (2021). Pyrolytic carbon black from truck tires: some new analytical approaches. Fullerenes, Nanotubes and Carbon Nanostructures, 29:304-314]. Finally, CBp-0 is a product with very low commercial value and cannot be used as a reinforcing material for new rubber composites because of its insufficient reinforcing ability and the presence of harmful PAHs.
[0002] WO2021 / 079395A1 describes a method suitable for purifying CBp-0 obtained from the pyrolysis of waste tires. In particular, WO2021 / 079395A1 describes two methods for purifying CBp-0: solvent extraction with zero toxicity and low environmental impact, which is suitable for removing pyrolytic rubber residues and PAHs; and heat treatment of CBp-0, which is suitable for evaporating the aforementioned pyrolytic rubber residues and PAHs. In particular, the heating process has proven to be more practical, faster, and more economical because it can be directly applied at the end of the pyrolysis of waste tires without having to separate CBp-0. In fact, as described in WO2021 / 079395A1, keeping CBp-0 at 600 °C - 700 °C for several tens of minutes under a nitrogen stream is sufficient to completely remove the residual asphalt fraction and the associated PAHs contained therein. The pyrolytic carbon black thus purified (called CBp-1 to distinguish it from the starting CBp-0) is free of pyrolytic rubber residues and PAHs, but there are still a series of problems that make it not particularly attractive to high-end tire manufacturers as a reinforcing material.
[0003] In particular, the main problem with CBp-1 is its high zinc and sulfur content. In fact, zinc sulfide (ZnS) is formed during the pyrolysis of waste tires and inevitably remains in CBp-1. If CBp-1 is used as a reinforcing filler in new compounds for tires or technical articles, the presence of ZnS can interfere with the vulcanization kinetics. Moreover, it is well known that zinc is toxic to aquatic microorganisms, certain fish, and other invertebrates [J.F. Skidmore, (1964). Toxicity of zinc compounds to aquatic animals, with special reference to fish. The Quarterly Review of Biology, 39:227-248; S.F. Brinkman, et al. (2012). Acute toxicity of zinc to several aquatic species native to the Rocky Mountains. Archives of Environmental Contamination and Toxicology, 62:272-281]. During rainwater leaching, zinc in ionic form is released into the environment through tires. Therefore, there is increasing concern about reducing the zinc content in rubber formulations, especially in tire formulations, with the aim of minimizing the spread of zinc in the environment. The presence of ZnS is not conducive to the widespread use of CBp-1 as an ecological material. Especially because the presence of ZnS does not perform any technical function; in fact, it interferes with the vulcanization kinetics. In fact, in rubber composites using CBp-1 as a filler, it is always necessary to add zinc oxide (ZnO) as a vulcanization activator.
[0004] WO2021 / 079395A1 describes a method for the acid purification of CBp-1, which is suitable for removing ZnS according to the general reaction:
[0005] ZnS + 2H + → Zn 2+ + H2S
[0006] This reaction can be carried out by using inorganic acids or biodegradable carboxylic acids derived from renewable sources. The purification treatment not only removes zinc and sulfur but also a series of transition metals, such as Cr, Co, Cd, Pb (which are considered toxic to living organisms and the environment), reducing their concentrations to very low levels. Therefore, the resulting product of CBp-1 purification is a product with high added value (referred to as CBp-2 in WO2021 / 079395A1 and hereinafter in this specification), and has low zinc and sulfur content and very low transition metal content, making it an ecological product.
[0007] However, CBp-2 may still contain varying amounts of silica also derived from the pyrolysis of waste tires. For the reuse of CBp-2 in new rubber composites, silica is not a problem. However, for certain specific applications, CBp completely free of silica may also be required. As described in WO2021 / 079395A1, silica can also be removed by changing the mixture of purification acidic reagents, thereby obtaining an absolutely clean product (referred to as CBp-3 in WO2021 / 079395A1 and hereinafter in this specification).
[0008] Table 1 - Chemical analysis of carbon black (CBp) obtained from pyrolysis of waste tires
[0009]
[0010]
[0011] Table 1 shows the X-ray fluorescence elemental analysis of products CBp-1, CBp-2, and CBp-3 and their respective ash contents compared to commercial CBp.
[0012] Table 1 shows that there is not much difference between commercial CBp and CBp-1 in terms of the content of certain transition metals or certain metalloids. As for the zinc, sulfur and ash contents, the differences between commercial CBp and CBp-1 are more obvious, which is related to the nature of the initial tires used for pyrolysis. However, for the purposes of the present invention, the source and nature of the tires used for pyrolysis are not important and should not be regarded as limiting factors. In fact, the present invention is applicable to CBp from any source. In addition, as shown in Table 1, the important thing is the excellent ecological quality, especially CBp-2 and CBp-3 from the purification method described in WO2021 / 079395A1. In fact, in CBp-2, the ash (mainly silica) is reduced to less than 7.5%, while it is almost absent in CBp-3. It is found that the content of iron (which is a promoter reused in the new rubber composite) in CBp-2 and CBp-3 is less than 0.02%, while the zinc (toxic to aquatic organisms, see [cited by Skidmore (1964); Brinkman, et al. (2012)]) reaches a negligible concentration of 0.07% in CBp-2 and CBp-3 from the initial value of more than 5% in CBp-1 through purification. Therefore, in CBp-2 and CBp-3, as a result of the purification process, the sulfur content of CBp-1 bound to zinc at least partially in the form of ZnS is reduced to 0.5-0.7%, thus reducing the risk of interfering with the vulcanization kinetics when CBp-2 and CBp-3 are used as reinforcing fillers in the new composite. The benefits of the purification of CBp-1 are also reflected in the content of certain transition metals such as Mn, Co, Ni and Pb. The concentrations of these metals are quite significant and important in the starting CBp-1 (see the case of Co), and are reduced to the lowest level in CBp-2 and CBp-3 due to purification. In the following Examples 1-5, the production and purification methods of pyrolytic carbon black described in WO2021 / 079395A1 are described in detail.
[0013] Example 1
[0014] In a rotary tube furnace, CBp-1 was produced by pyrolysis of end-of-life tires (hereinafter referred to as ELT) as described below. The furnace was loaded with 3500 g of scrapped tires, pre-ground to 325 mesh. The load of tire powder was heated to 600 °C and held at this temperature until pyrolysis was complete, at which time approximately 1150 g of residual carbon black remained in the reactor. After pyrolysis was complete, the resulting CBp was heated to 660 °C and held at this temperature for 75 minutes under a nitrogen stream. Alternatively, it could be heated to 700 °C under a nitrogen stream and held at this temperature for 45 minutes to complete the "cleaning" of CBp, removing pyrolyzed rubber residues and PAHs and generating CBp-1. The resulting CBp-1 collected from the reactor and cooled to room temperature was transferred in an amount of 1000 g to a 5 L Duran glass jacketed reactor equipped with a stirrer. A bubble cooler connected to a Dreschel bottle containing 1 L of 10% NaOH solution by a tap, a valve for introducing an inert gas (such as nitrogen), and a dropping funnel containing 3000 ml of 20% hydrochloric acid were placed on top of the reactor. Purification was carried out by allowing hydrochloric acid to fall rapidly onto CBp-1 under stirring, thereby producing a fluid slurry. The reactor was heated to a temperature of 60 to 90 °C to facilitate purification. Hydrochloric acid reacts with zinc sulfide present in CBp-1 (if derived from OTR (off-road) tires, its content is up to 82 g / kg; if derived from PSR (passenger car) tires, i.e., passenger car tires, or TBR (truck and bus) tires, such as truck and bus tires, the ZnS content is significantly lower) and decomposes it according to the following reaction:
[0015] ZnS + 2HCl → ZnCl2 + H2S
[0016] Zinc is leached and enters the aqueous solution, while hydrogen sulfide is released in gaseous form and is transported by a stream of nitrogen (or another inert gas, such as compressed air) to the Dreschel bottle, where it bubbles in the NaOH solution and is trapped in the NaOH solution as sodium sulfide:
[0017] H2S + 2NaOH → Na2S + 2H2O
[0018] The purification reaction is relatively fast, and the removal of zinc is almost completed within 30 minutes. Then, the reaction slurry is filtered through a Buchner funnel, and the CBp-2 filter cake formed on the filter paper is washed repeatedly with water until the wash water shows neutrality (at least pH = 5.5 - 6.0). At this time, the wet cake of CBp-2 is transferred to a dryer, where the residual water is completely removed. The yield of purified CBp-2 is 91.5% of the starting CBp-1 (the yield can be higher than 91.5%, depending on the ELT mixture from which CBp-1 is derived). Analysis of CBp-2 by X-ray fluorescence shows the analytical composition reported in Table 1, while the ash content is determined by thermogravimetric curve analysis in an air stream up to 850 °C. The surface area of CBp-2 measured by nitrogen absorption (B.E.T. method) shows a value of 65 to 70 m 2 / g, as reported in Table 1.
[0019] Example 2
[0020] It is carried out exactly as in Example 1, with the only difference being that the purification mixture consists of 3000 mL of 6.0 M hydrochloric acid and 3.0 M hydrofluoric acid. In this case, the purification is not limited to dissolving zinc and removing sulfur by decomposing ZnS as in Example 1, as it has also been shown to be effective in dissolving and removing silica present in CBp-1. In fact, HF dissolves silica according to the following reaction:
[0021] 6HF + SiO2 → H2SiF6 + 2H2O
[0022] It dissolves it in the form of hexafluorosilicic acid. Silica is present in CBp-1 because it is currently widely spread as a reinforcing filler, and it is added to tire compounds in the same way as furnace black as a reinforcing filler. The subsequent operations of filtering and drying the resulting CBp-3 are the same as those described in Example 1. Analysis of the resulting CBp-3 by X-ray fluorescence shows the elemental composition reported in Table 1, while the ash content of CBp-3 is determined by thermogravimetric curve analysis in an air stream up to 850 °C. As expected, CBp-3 shows complete absence of ash. The surface area of CBp-3 measured by nitrogen absorption (B.E.T. method) shows a value of 65 to 70 m 2 / g.
[0023] Generally speaking, compared with the expected values of surface area measurement, the reinforcing ability of commercial CBp-1 is limited. Apparently, despite the large surface area of CBp-1, its surface is not very active and is hardly suitable for the chemisorption and physical adsorption processes that form the basis of the reinforcing mechanism of rubber composites. The same problem also exists in the cases of CBp-2 and CBp-3 in Examples 1 and 2. Like commercial CBp-1, CBp-2 and CBp-3 both undergo a conventional grinding process, more precisely micronization, before being reused in rubber composites. Micronization breaks down carbon black aggregates and some agglomerates, reducing the diameter of the aggregates to below 40 μm. Micronization helps the dispersion of CBp in the rubber matrix and improves its reinforcing ability. However, despite micronization, the reinforcing effects of various types of CBp are generally lower than expected.
[0024] The solution according to the present invention is suitable for this situation; its purpose is to provide a method for recycling carbon black obtained from the pyrolysis of waste tires, which can overcome the limitations of the purification methods in the prior art.
[0025] According to the present invention, these and other results are obtained by proposing a method for recycling carbon black obtained from the pyrolysis of waste tires, which method comprises the following steps:
[0026] - Heat-treat the carbon black in an inert atmosphere at a temperature of 550 °C to 800 °C to obtain purified carbon black (CBp-1),
[0027] Optionally further purify by subsequent steps:
[0028] - Selectively extract zinc from the purified carbon black (CBp-1) using an aqueous solution containing a carboxylic acid selected from citric acid and tartaric acid or an inorganic acid selected from hydrochloric acid and sulfuric acid, preferably an inorganic acid selected from hydrochloric acid and sulfuric acid, to obtain purified carbon black (CBp-2) with low zinc and sulfur contents,
[0029] The aqueous solution optionally further contains hydrofluoric acid, in combination with the carboxylic acid or the inorganic acid, to obtain purified carbon black (CBp-3) with low silica content,
[0030] This method further comprises the following steps:
[0031] - Activate the surface of the purified carbon black using a reactive gas selected from nitrogen, argon, carbon dioxide, superheated steam, and mixtures thereof, preferably a mixture selected from carbon dioxide, superheated steam, and mixtures thereof.
[0032] Preferably, according to the present invention, the heat treatment in an inert atmosphere is carried out at a temperature of 600 °C to 780 °C and under an inert gas flow selected from the following: N2, Ar, CO2, superheated steam, or a combination thereof.
[0033] In particular, also according to the invention, said step of activating the surface of the purified carbon black with a reactive gas is carried out by a flow of CO2 and / or superheated steam of 150 to 400 ml / min, a heating rate of 10 to 40°C / min, up to a final temperature of 800 to 950°C, with a residence time at this final temperature of 30 to 60 minutes.
[0034] Another object of the present invention is the recycled carbon black obtained by the aforementioned process, and the use of this recycled carbon black in the production of rubber compounds.
[0035] According to the present invention, it has surprisingly been discovered that, by performing a surface etching (or surface activation) step on micronized CBp-1, CBp-2, and CBp-3 with a reactive gas, it is possible not only to control and, in particular, to increase the surface area of the carbon black, but also to activate the surface, making it richer in active sites and thus more susceptible to chemical and physical adsorption of rubber, thereby ultimately not only equaling but even exceeding the reinforcing effect of "furnace" carbon black ("furnace" carbon black is conventional carbon black obtained from petroleum). In other words, a method has been discovered for reactivating the surface of CBp-1, and in particular CBp-2 and CBp-3, by surface etching with a reactive gas. This treatment results in a considerable and surprising reinforcing effect of CBp-2 and CBp-3, when used as reinforcing fillers in new rubber compounds, that is not observed with similar unactivated CBp. Therefore, CBp-2 and CBp-3, in addition to being eco-carbon blacks (since they do not contain zinc, sulfur, toxic transition metals and silicon dioxide (in the case of CBp-3)), also become highly reinforced carbon blacks after etching treatment with reactive gases, as detailed in Example 3 below.
[0036] Examples 3 - 5
[0037] A Carbolite-Gero horizontal "TSO Rotary Reactor Tube Furnace" equipped with a semi-rotating grooved quartz reactor vessel was charged with 300 g of CBp-1, CBp-2 or CBp-3 (as detailed in Table 2). The above-mentioned pyrolytic carbon blacks had been micronized and sieved <40 μm. As shown in Table 2, the selected CBp was heated to 800°C or another temperature under a continuous flow of carbon dioxide (CO2). This temperature was then maintained for a predetermined time (as detailed in Table 2), again under a continuous gas flow, while the preselected CBp powder was remixed under the semi-rotating motion of the quartz reactor vessel. At the end of the treatment, it was cooled to room temperature, again strictly under a CO2 flow. The selected CBp activated with reactive gas was analyzed, the results of which are shown in Table 2, and subsequently used for testing in rubber compounds in subsequent examples.
[0038] The effect of the reaction gases is evident in Table 2: they result in a significant increase in the surface area of CBp, and in fact, the surface area can be simply controlled by varying the reaction temperature (as shown in Table 2) or the reaction time. After such treatment, the surface area of CBp can even double compared to the starting value of the crude CBp. In fact, as shown in Table 2, CBp-1 increases from an initial 50 m 2 / g to 98 m 2 / g, while CBp-2 and CBp-3 increase from an initial 65 - 70 m 2 / g to values exceeding 110 m 2 / g. Another effect of CO2 on the pyrolytic carbon black is to impart a certain degree of microporosity to the treated carbon black, which is almost absent in the starting CBp. Given that the surface area is measured by the standard B.E.T. method according to ASTM D - 6556, the microporosity is determined by the difference between the value of the B.E.T. surface area and the value of the STSA (statistical thickness surface area) procedure, also according to the standard of ASTM D - 6556. In the absence of microporosity, the B.E.T. and STSA surface areas are identical, and the value obtained from the difference [B.E.T.] - [STSA] corresponds to the microporosity value.
[0039] [The following table]
[0040] Table 2 - Examples 3 - 5 relate to the activation of pre - micronized CBp - 1, CBp - 2, and CBp - 3
[0041]
[0042] ( * ) Obtained according to the patented method in WO2021 / 079395A1 and Examples 1 - 3
[0043] To further characterize CBp - 1, CBp - 2, and CBp - 3 of the aforementioned Examples 3 - 5, a series of structural parameters were determined by X - ray diffraction, using a conventional so - called "furnace - process" carbon black as the reference carbon black, which is derived from petroleum and has the ASTM code N772. The basic structural parameters commonly used to "fix" the structural characteristics of amorphous carbon black are obtained from X - ray diffraction data.
[0044] For example, Ismagilov, Z.R., et al. (2019). Structural analysis of needle coke. Coke and Chemistry, 62:135 - 142 details the formulas for calculating these parameters, and the parameters calculated from the X - ray diffraction patterns of N772 and each CBp are shown at the bottom of Table 3, including the interplanar spacing (d) of the graphene planes 002) The packing density (ρ) of the graphene plane, the longitudinal dimension (La) of the structural plane, the thickness (Lc) of the stacked graphene layers, and finally the number of graphene layers (N) in each "grain". From the structural parameters reported in Table 3, one can infer a considerable structural similarity between the reference "furnace black" carbon black N772 and the carbon blacks CBp-1, CBp-2, and CBp-3 obtained from waste tire pyrolysis, and in the latter two cases, they were obtained after sufficient acid purification.
[0045] Table 3 - Structural parameters of CBp determined by X-ray diffraction, compared with furnace black N772 as a reference
[0046]
[0047] Another characterization result obtained from the X-ray diffraction analysis of unactivated CBp-1 is the presence of ZnS in a crystalline modification called sphalerite, which is easily identified by the presence of reflections X at 2θ = 28.450; 47.435; 56.269. The polymorph formed at high temperature of sphalerite is a crystalline modification of ZnS called wurtzite. The X-ray diffraction of thermally activated CBp-1 differs from that of unactivated CBp-1 in the presence of wurtzite, with characteristic reflections at 2θ = 26.8074; 28.4810; 30.460; 39.453; 47.4579; 51.662; 56.289. CBp-2 and CBp-3 (whether activated or unactivated) in terms of the characteristics under X-ray diffraction analysis involve the complete absence of any reflections due to the crystal structures of sphalerite or wurtzite, and all the zinc present has been completely removed through the purification process.
[0048] As shown in the following examples, it was further surprisingly found that if the pyrolysis carbon black obtained from ELTs, purified according to Examples 1-2, and activated according to Examples 3-5 is used as a reinforcing material in rubber composites, the reinforcing effect produced is significantly better than that conferred by commercial CBp or even "furnace black" carbon black (i.e., carbon black derived from petroleum, such as carbon black N772). Therefore, an object of the present invention is the surface activation of CBp-1, CBp-2, and CBp-3 according to Examples 3-5 and the subsequent surprising reinforcing effect conferred on the rubber composites of Examples 6-12.
[0049] Examples 6 - 12
[0050] Pyrolytic carbon black from ELT CBp-1 prepared according to patent WO2021 / 079395A1, and pyrolytic carbon blacks CBp-2 and CBp-3 prepared as described in Examples 1 and 2, were activated as described in Examples 3-5 and then tested in the following standard natural rubber-based formulation: natural rubber (cis-1,4-polyisoprene from the Hevea brasiliensis tree, type CV60): 100 phr (“phr” means the number of parts of each ingredient in the formulation added per 100 parts of rubber and is a method of representing typical rubber formulations in this industry); carbon black: 52 phr (“furnace” carbon black, i.e., carbon black derived from petroleum, which is N330, N550, and N772 and is used as a reference material, while CBp-1, CBp-2, or CBp-3 prepared according to Examples 3-5 is used as pyrolytic carbon black. Commercial CBp was also used as a further reference material); T-DAE type plasticizer oil (treated distillate aromatic extract, i.e., having aromatic properties): 5 phr; stearic acid: 1 phr; zinc oxide (3 phr); IPPD (isopropyl-N-phenyl-p-phenylenediamine) as an antiozonant: 1.5 phr; TMQ (polymerized trimethylquinoline) as an antioxidant: 1 phr; sulfur: 1.5 phr; and CBS (cyclohexylbenzothiazole sulfenamide) as an accelerator: 1.5 phr.
[0051] Each rubber composite of Examples 6 - 12 was prepared using a 1.5 - liter laboratory mixer (Banbury) that allows preparation of >1 kg of composite per batch. Considering the proportions of the formulation, the components of the composite formulated in the previous paragraph were carefully weighed. The order of addition to the mixer first included the rubber, and then the machine was allowed to stir for several minutes. Then the carbon black (the only component that differed between composites in Examples 6 - 12, and for each example, the type added is shown in Table 4) was added together with the plasticizer oil. The carbon black was thoroughly mixed with the rubber and the oil, and finally zinc oxide, stearic acid, antiozonant, and antioxidant were added. Mixing was continued until a homogeneous composite was obtained, which was then unloaded from the Banbury and reduced to a thin layer approximately 0.5 cm thick by repeatedly passing it through a special grinder known to those skilled in the art. The composite thus prepared was cooled at room temperature. After cooling, the composite was loaded into the Banbury again, and after weighing, the vulcanizing agents (sulfur and accelerator) were added to conform to the proportions of the formulation. Mixing was continued until a homogeneous composite was obtained. The composite thus obtained was unloaded from the Banbury and then reduced to a thin layer by repeatedly passing it through the grinder, and subsequently cooled at room temperature. For vulcanization, according to ASTM or UNI standards (the standards followed for each technical test are shown in Table 4), an amount of the composite sufficient to fill the test specimen mold was extracted for technical testing and vulcanized in a press, heated at 160 °C for 15 min in the case of thin specimens and 20 min in the case of larger specimens. The vulcanized specimens were subjected to technical tests according to ASTM or UNI standards. Each standard selected and applied in the technical tests is shown in Table 4.
[0052] Table 4 - Natural rubber - based composites (NR, cis - 1,4 - polyisoprene)
[0053]
[0054]
[0055] For illustrative purposes, the natural rubber - based formulations of the examples in Table 4 were selected as standard composites, preferentially but not exclusively for composites of the rubber components of truck tires or other composites of the general rubber industry.
[0056] From the mechanical property data shown in Table 4, it is immediately possible to infer the surprising reinforcing effect exerted by the activated pyrolytic carbon blacks CBp-1, CBp-2 and CBp-3 according to Examples 3-5, compared to, for example, commercial CBp. To highlight this surprising reinforcing effect, it is necessary to consider the data related to the modulus or tensile strength shown in Table 4. It can be observed that the measured values of the composites prepared with the activated CBp-1, CBp-2 and CBp-3 according to Examples 3-5 are significantly higher than those of commercial CBp. This demonstrates the greater reinforcing effect of the activated CBp-1, CBp-2 and CBp-3 according to Examples 3-5, which is due to the surface treatment carried out, which makes them, for all intents and purposes, equivalent in performance to conventional carbon blacks (the "furnace" carbon blacks obtained from petroleum) such as N330, N550 and N772, which were studied as reference materials in Table 4. In particular, the comparison between the modulus and the tensile strength of the composites prepared with the activated CBp-1, CBp-2 and CBp-3 according to Examples 3-5 shows surprising values, even superior to the performance of furnace blacks N772 and N550. The excellent properties of the activated CBp-1, CBp-2 and CBp-3 according to Examples 3-5 are reflected in the natural rubber-based composites in Table 4, in terms of high tear strength and minimum abrasion loss, as well as the response to permanent deformation, compared to commercial CBp and also compared to the "furnace" carbon blacks N772 and N550. From a viscoelastic point of view, the activated CBp-1, CBp-2 and CBp-3 according to Examples 3-5 show low mechanical hysteresis, which is a much desired property for applications in tyre compounds, where low hysteresis means that, obviously with the same composite formulation, less rolling energy is dissipated in the form of heat compared to other carbon blacks, and ultimately less fuel consumption. For the hypothetical application of natural rubber-based composites to truck tyres, the combination of a high modulus value and a high tensile strength is one of the desired qualities for the application, since these properties themselves manifest as a long product life and high tear strength (confirmed for the activated CBp-1, CBp-2 and CBp-3 according to Examples 3-5 compared to commercial CBp in Table 4), as well as excellent abrasion resistance compared to commercial CBp, in mm of material worn in the abrasion resistance test 3It is shown that CBp-1, CBp-2, and CBp-3 activated according to Examples 3-5 exhibit a significantly smaller volume of the wear material than the measured values of commercial CBp (see Table 4). Regarding the permanent deformation test, in Table 4, for the activated CBp-1, CBp-2, and CBp-3 according to Examples 3-5, a lower permanent deformation can be observed compared to commercial CBp (a property desired for application purposes). Finally, both resilience and viscoelasticity are used to measure the dynamic mechanical properties of the composite, especially mechanical hysteresis. As mentioned above, for tire applications, mechanical hysteresis must be as low as possible to minimize fuel consumption. A higher elastic modulus (E′) is in turn a more significant manifestation of the reinforcing effect exerted by the fillers under consideration, also under dynamic conditions. In Table 4, we can in fact see that the composites prepared with the activated CBp-1, CBp-2, and CBp-3 according to Examples 3-5 exhibit a significantly higher elastic modulus than the composites containing commercial CBp. Thus, the activated carbon blacks CBp-1, CBp-2, and CBp-3 according to Examples 3-5 and including acid purification and thermal activation, as detailed in this patent, result in products with surprising reinforcing properties of absolute technical value, due to their low environmental impact (see Table 1) and excellent technical properties in natural rubber composites, as shown in Table 4.
[0057] Examples 13 - 19
[0058] The pyrolytic carbon black from ELT CBp-1 prepared according to Patent WO2021 / 079395A1, and the pyrolytic carbon blacks CBp-2 and CBp-3 prepared as described in Examples 1 and 2 were activated according to Examples 3-5 and subsequently tested with the following standard styrene-butadiene copolymer formulation: S1502: 100 phr (“phr” represents the number of parts of each component in the formulation added per 100 parts of rubber and is a typical method used by those skilled in the art to express rubber formulations); carbon black: 52 phr (“furnace” carbon black, i.e., derived from petroleum, N330, N550, and N772 were used as reference materials, while CBp-1, CBp-2, or CBp-3 was the carbon black prepared according to Examples 3-5; commercial CBp was also used as a further reference); T-DAE type plasticizer oil (treated distillate aromatic extract, i.e., having aromatic properties): 5 phr; stearic acid: 1 phr; zinc oxide (3 phr); IPPD (isopropyl-N-phenyl-p-phenylenediamine) as an antiozonant: 1.5 phr; TMQ (polymerized trimethylquinoline) as an antioxidant: 1 phr; sulfur: 1.5 phr, CBS (cyclohexylbenzothiazole sulfenamide) as an accelerator: 1.0 phr, TBzTD (tetrabenzylthiuram disulfide) as an accelerator: 0.3 phr, and DPG-80 (80% diphenylguanidine) as an accelerator: 0.2 phr.
[0059] Each of the rubber compounds of Examples 13 - 19 was prepared using a 1.5 - liter laboratory mixer (Banbury) that allows preparation of >1 kg of compound per batch. Considering the proportions of the formulation, the components of the compound formulated in the previous paragraph were carefully weighed. The order of addition to the mixer first included the rubber, and then the machine was agitated for several minutes. Then the carbon black, which is the only component that differs between the compounds of Examples 13 - 19, and for each example, the type added is shown in Table 5, was added together with the plasticizing oil. The carbon black was allowed to mix well with the rubber and the oil, and finally zinc oxide, stearic acid, antiozonant, and antioxidant were added. Mixing was continued until a homogeneous compound was obtained, and then it was unloaded from the Banbury and reduced to a thin layer approximately 0.5 cm thick by repeatedly passing it through a special grinder known to those skilled in the art. The compound thus prepared was cooled at room temperature. After cooling, the compound was loaded into the Banbury again, and after weighing, the vulcanizing agents (sulfur and various accelerators) were added to conform to the proportions of the formulation. Mixing was continued until a homogeneous compound was obtained. The compound thus obtained was unloaded from the Banbury and reduced to a thin layer approximately 0.5 cm thick by repeatedly passing it through the grinder, and then cooled at room temperature. For vulcanization, according to ASTM or UNI standards (the standards followed for each technical test are shown in Table 5), an amount of the compound sufficient to fill the test specimen mold was extracted for technical testing and vulcanized in a press, heated at 160 °C for 15 min in the case of thin specimens and 20 min in the case of larger specimens. As described above, the vulcanized specimens were subjected to technical testing according to ASTM or UNI standards. Each of the standards selected and applied in the technical testing is shown in Table 5.
[0060] For illustrative purposes, the styrene - butadiene copolymer - based formulation of the examples in Table 5 was selected as a standard compound, preferentially but not exclusively for compounds of the rubber components of automotive tires or other compounds of the general rubber industry.
[0061] Similarly, in this type of SBR-based polymer matrix, from the mechanical property data shown in Table 5, it can be immediately inferred that the pyrolytic carbon blacks CBp-1, CBp-2, and CBp-3 prepared according to Examples 3-5 exhibit a surprising and unexpected reinforcing effect compared to the reinforcing properties provided by, for example, a commercial CBp used as a reference material. In fact, the data reported in Table 5 related to the modulus or tensile strength show that the values of the composites prepared with the activated CBp-1, CBp-2, and CBp-3 according to Examples 3-5 are surprisingly higher compared to the commercial CBp. This demonstrates that due to the surface treatment carried out in Examples 3-5, CBp-1, CBp-2, and CBp-3 have a greater reinforcing effect, making them, for all intents and purposes, comparable in performance to conventional carbon blacks (the "furnace process" carbon blacks obtained from petroleum) such as N330, N550, and N772, which were studied as reference materials in Table 5. The surprising and excellent properties of the activated CBp-1, CBp-2, and CBp-3 according to Examples 3-5 are also reflected in the SBR-type polymer matrix of Table 5, where their performance is significantly better than that of the commercial CBp in terms of tear strength and abrasion loss, as well as in response to permanent deformation.
[0062] Similarly, from the viscoelasticity perspective, the activated CBp-1, CBp-2, and CBp-3 according to Examples 3-5 exhibit low mechanical hysteresis (tanδ), comparable to or better than that of carbon blacks N330, N550, N772 from petroleum and the commercial pyrolytic carbon black CBp. The results obtained by measuring the tanδ value are further confirmed by the measurement of the resilience value. Low mechanical hysteresis is highly desirable in tire applications as it is directly related to a reduction in fuel consumption.
[0063] Table 5 - Styrene-butadiene copolymer-based composites (SBR)
[0064]
[0065] Furthermore, in terms of the elastic modulus E’, the three CBps of this patent outperform the commercial CBp and the carbon black ASTM N772 in terms of performance, and this result also confirms better reinforcement under dynamic conditions.
[0066] Examples 20 - 26
[0067] Pyrolytic carbon black from ELT CBp-1 prepared according to patent WO2021 / 079395A1, and pyrolytic carbon blacks CBp-2 and CBp-3 prepared according to Examples 1 and 2, were activated according to Examples 3-5 and then tested in the following standard acrylonitrile-butadiene copolymer-based formulation: NBR3345: 100 phr ("phr" represents the number of parts of each component in the formulation added per 100 parts of rubber and is a method of representing typical rubber formulations in the industry); carbon black: 52 phr ("furnace" carbon black, i.e., derived from petroleum, is N330, N550, and N772 and is used as a reference material, while the carbon blacks prepared according to the present invention are CBp-1, CBp-2, or CBp-3; commercial CBp was also used as a further reference); DINP type plasticizer (diisononyl phthalate): 5 phr; stearic acid: 1 phr; zinc oxide (3 phr); IPPD (isopropyl-N-phenyl-p-phenylenediamine) as an antiozonant: 1.5 phr; TMQ (polymerized trimethylquinoline) as an antioxidant: 1 phr; sulfur: 1.5 phr, CBS (cyclohexylbenzothiazole sulfenamide) as an accelerator: 1.0 phr; and TBzTD (tetrabenzylthiuram disulfide) as an accelerator: 0.3 phr.
[0068] Each of the rubber composites of Examples 20 - 26 was prepared using a 1.5 - liter laboratory mixer (Banbury) that allows preparation of > 1 kg of composite per batch. Considering the proportions of the formulation, the components of the composite formulated in the previous paragraph were carefully weighed. The order of addition to the mixer first included the rubber, and then the machine was stirred for several minutes. Then the carbon black (the only component that differed between the composites in Examples 20 - 26, and for each example, the type added is shown in Table 6) was added together with the plasticizer oil. The carbon black was allowed to mix well with the rubber and the oil, and finally zinc oxide, stearic acid, anti - ozone agent, and antioxidant were added. Mixing was continued until a homogeneous composite was obtained, which was then unloaded from the Banbury and reduced to a thin layer approximately 0.5 cm thick by repeatedly passing it through a special grinder known to those skilled in the art. The composite thus prepared was cooled at room temperature. After cooling, the composite was loaded into the Banbury again, and after weighing, the vulcanizing agents (sulfur and various accelerators) were added to conform to the proportions of the formulation. Mixing was continued until a homogeneous composite was obtained. The composite thus obtained was unloaded from the Banbury and reduced to a thin layer approximately 0.5 cm by repeatedly passing it through the grinder, and then cooled at room temperature. For vulcanization, according to ASTM or UNI standards (the standards followed for each technical test are shown in Table 6), an amount of the composite sufficient to fill the test specimen mold was extracted for technical testing and vulcanized in a press, heated at 160 °C for 15 min in the case of thin specimens and 20 min in the case of larger specimens. The vulcanized specimens were subjected to technical testing according to ASTM or UNI standards. Each standard selected and applied in the technical testing is shown in Table 6.
[0069] For illustrative purposes, the acrylonitrile - butadiene copolymer - based composite (NBR) selected for the examples in Table 6 was used as a standard composite for molded technical articles made of rubber in applications other than tires. In other words, by using this NBR - based composite, it was intended to show that the activated pyrolytic carbon blacks CBp - 1, CBp - 2, and CBp - 3 according to Examples 3 - 5, if used as reinforcing materials in composites other than tires, can also produce surprising technical advantages and are thus particularly suitable for general technical articles.
[0070] As shown in Table 6, in the NBR-based polymer matrix, as has been seen from the previous NR-based and SBR-based matrices, the pyrolytic carbon blacks CBp-1, CBp-2, and CBp-3 confirmed the surprising and excellent reinforcing effects previously observed in natural rubber-based and SBR-based composites, such as compared to commercial CBp. In fact, from the data related to the modulus or tensile strength shown in Table 6, it can be observed that the measured values of the composites prepared with the activated CBp-1, CBp-2, and CBp-3 according to Examples 3-5 are significantly higher compared to commercial CBp. This demonstrates that CBp-1, CBp-2, and CBp-3 have a greater reinforcing effect due to the surface treatment, which makes them, for all intents and purposes, comparable in performance to the currently used traditional "furnace process" carbon black derived from petroleum.
[0071] [Following table]
[0072] Table 6 - Acrylonitrile-Butadiene Copolymer-Based Composites (NBR)
[0073]
[0074] The NBR-based formulations of Examples 20-26 are composites for technical articles designed essentially for static applications. For this very reason, neither viscoelasticity nor abrasion resistance was measured. However, in this case, CBp-1, CBp-2, and CBp-3 showed better mechanical hysteresis compared to commercial CBp, as measured by resilience. Also, in terms of permanent deformation, the activated CBp-1, CBp-2, and CBp-3 according to Examples 3-5 outperform commercial CBp in performance due to the lower permanent deformation.
[0075] It has thus been found, and it is thus also an object of the present patent, that the pyrolytic carbon blacks CBp-1, CBp-2 and CBp-3 obtained from waste tyres - the latter two being pre-purified to remove unwanted components (zinc, transition metals and sulphur in CBp-2, and silica in CBp-3) - and all activated according to Examples 3-5, when tested as reinforcing materials in composites based on natural rubber or cis-1,4-polyisoprene (NR or IR) (Examples 6-12), based on styrene-butadiene copolymer (SBR) (Examples 13-19) or based on acrylonitrile-butadiene copolymer (NBR) (Examples 20-25), produce (in all cases) a surprising and excellent reinforcing effect, which is measured by the values of the modulus and tensile strength, e.g. completely exceeding the performance of commercial CBp and being equal to or even exceeding the performance of certain "furnace" carbon blacks obtained from petroleum (such as N772, N550 and N330). According to Examples 3-5 and the object of the present patent, the surprising properties of the activated CBp-1, CBp-2 and CBp-3 also extend to other mechanical properties, such as excellent tear strength, minimal abrasion loss, limited permanent deformation and low mechanical hysteresis measured according to tanδ and resilience, and in some respects are completely superior to the performance of commercial CBp and certain "furnace" carbon blacks (such as N772 and N550).
Claims
1. A method for recovering carbon black obtained from the pyrolysis of waste tires, comprising the following steps: - Heat-treat the carbon black in an inert atmosphere at a temperature of 550 °C to 800 °C to obtain purified carbon black (CBp-1), - Activate the surface of the purified carbon black using a reactive gas selected from nitrogen, argon, carbon dioxide, superheated steam, and mixtures thereof, preferably a reactive gas selected from carbon dioxide, superheated steam, and mixtures thereof, at a temperature of 800 °C to 1000 °C.
2. The method for recovering carbon black obtained by pyrolysis of waste tires according to claim 1, characterized in that, After the heat-treatment step and before the step of activating the surface of the purified carbon black, it further comprises the following steps: - Selectively extract zinc from the purified carbon black (CBp-1) using an aqueous solution containing a carboxylic acid selected from citric acid and tartaric acid or an inorganic acid selected from hydrochloric acid and sulfuric acid, preferably an inorganic acid selected from hydrochloric acid and sulfuric acid, to obtain purified carbon black (CBp-2) with low zinc and sulfur content, or purified carbon black (CBp-2) with low zinc content.
3. The method for recovering carbon black obtained by pyrolysis of waste tires according to claim 2, characterized in that, The aqueous solution further contains hydrofluoric acid, combined with the carboxylic acid or inorganic acid according to claim 2, to obtain purified carbon black (CBp-3) with low silica content.
4. A method for recovering carbon black obtained by pyrolysis of waste tires according to any one of the preceding claims, characterized in that, The heat-treatment in the inert atmosphere is carried out at a temperature of 600 °C to 780 °C.
5. A method for recovering carbon black obtained by pyrolysis of waste tires according to any one of the preceding claims, characterized in that, The heat-treatment in the inert atmosphere is carried out under an inert gas flow selected from the following: N2, Ar, CO2, superheated steam, and combinations thereof.
6. The method for recovering carbon black obtained by pyrolysis of waste tires according to any one of the preceding claims, characterized in that, The step of activating the surface of the purified carbon black using the reactive gas is carried out by a CO2 and / or superheated steam flow of 150 to 400 ml / min, with a heating rate of 10 °C / min to 40 °C / min, reaching a final temperature of preferably 800 °C to 950 °C, and a residence time at the final temperature of 30 to 60 minutes.
7. A recovered carbon black obtained from the method according to claims 1-6.
8. Use of the recovered carbon black according to claim 7 in the production of rubber composites.
9. A rubber composite based on natural rubber (NR, cis-1,4-polyisoprene), which contains the recovered carbon black according to claim 7.
10. A rubber composite based on styrene-butadiene copolymer (SBR), which contains the recovered carbon black according to claim 7.
11. A rubber composite based on acrylonitrile-butadiene copolymer (NBR), which contains the recovered carbon black according to claim 7.
12. A rubber composite based on the following mixtures: natural rubber (NR, cis-1,4-polyisoprene) and / or styrene-butadiene copolymer (SBR) and / or polybutadiene homopolymer (BR) and / or acrylonitrile-butadiene copolymer (NBR) and / or ethylene-propylene-diene copolymer (EPDM) and / or ethylene-propylene copolymer (EPM) and / or chloroprene or neoprene and / or butyl rubber and / or chlorobutyl rubber and / or bromobutyl rubber and / or ethylene-vinyl acetate rubber and / or chlorinated polyethylene and / or chlorosulfonated polyethylene rubber and / or acrylic rubber and / or epichlorohydrin rubber and / or fluorinated elastomer rubber and / or silicone rubber and / or fluorosilicone rubber and / or polyester and polyether rubber and / or polyurethane elastomer and / or thermoplastic elastomer, the rubber composite comprising the recycled carbon black according to claim 7.
Citation Information
Patent Citations
Microscope
WO2013190058A1
Error compensation in analog neural networks
WO2020260067A1
Ecological purification and reactivation process of carbon black obtained from the pyrolysis of used tyres
WO2021079395A1